LOADBEARING CAPACITY OF LSF WALLS UNDER FIRE EXPOSURE - Piloto, Paulo A G; Khetata, Mohamed S; Gavilán, Ana B R (MATTER: International Journal of Science and Technology, 2018)
Light steel frame (LSF) (LSF) and prefabricated panels are widely used in loadbearing walls, with direct application to steel framed buildings. These walls are made with steel cold formed sections (studs and tracks) using gypsum plasterboard and other material layers attached to the flanges and sometimes insulation material in the cavities. The fire resistance is usually provided by one or more layer of materials and or by the cavity insulation. This investigation evaluates the fire resistance of the loadbearing walls, from the point of view of insulation (I) and loadbearing capacity (R). Experimental results obtained from partition walls were used into the numerical model to accurately preview the cracking, falling off and the ignition of combustible material. The numerical model was validated under the same fire conditions. The loadbearing capacity is determined using this hybrid model. This model is able to predict an accurate fire resistance for any load level, taking into account the brittle behaviour of gypsum panels and the ignition of combustible materials. The loadbearing decreases with the increase of the load level. A new formula is presented to determine the critical average temperature of the LSF.